Customization in Standard Hierarchy Report for Improving Activity Based Costing Process - Taufiq Maulana Firdaus; Muhardi Saputra; Tien Fabrianti Kusumasari (International Journal of Innovation in Enterprise System, 2022)
Activity based costing process is a process to accurately manage the cost allocation process for aproduct. With the development of technology, the activity-based costing process has been integratedwith the ERP system so that it can relate to all business processes as a whole and can reduce expensesto manage the flow of information systems within the company. It is necessary to determine a fastbusiness process for the allocation of these costs so that a product can be produced. A standardhierarchy is needed which serves as the center of the business process for determining the activitybased costing process. This process is still done manually so that it slows down the businessdetermination process in the activity-based costing process. This research will implement the searchfunction in the ABC system by creating a reporting system that can search business processes in thestandard hierarchy in SAP S/4HANA. This research will use SEEM embed with SDLC method wherethis method pays attention from the perspective of the user and the company to produce an efficientABC process with the company's objectives.